School success for kids with ADHD - Silverman, Stephan, 1942- (Routledge, 2021)
School Success for Kids With ADHD offers parents and teachers the support they need to ensure that children with attention deficits build on their strengths, circumvent their weaknesses, and achieve to their fullest potential. With the growing number of children diagnosed with attention problems, parents and teachers need practical advice for helping these children succeed in school. Topics covered include recognizing the causes and types of attention deficits and how they appear in the school context, requesting school evaluations and diagnoses, understanding the laws regarding students with special needs, advocating for these students in the school environment, and coaching students with attention deficits to success. The authors also include a brief overview of research and medical perspectives on attention deficits, strategies used by teachers of children with ADHD, and helpful tools for parents and teachers to employ.